Critical issues in early Israelite history - Hess, Richard S.; Klingbeil, Gerald A., 1964-; Ray, Paul J. (Bulletin for biblical research supplements, 2008)
Today, the mainstream opinion is that there was no Conquest, and the Israelites, if they can be identified as a national entity or as a people, did not arrive in Canaan by means of a military conquest. For three days in March 2004, a group of scholars met to consider the state of the question and to provide a response to the predominant academic skepticism, a response that considers the biblical text to be an important datum in the construction of the history of the people of Israel. Critical Issues in Early Israelite History publishes the papers read at this conference. --from publisher description.